2016
DOI: 10.3390/s16101773
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Reconstruction for Micro Defect Detection in Acoustic Micro Imaging

Abstract: Acoustic micro imaging has been proven to be sufficiently sensitive for micro defect detection. In this study, we propose a sparse reconstruction method for acoustic micro imaging. A finite element model with a micro defect is developed to emulate the physical scanning. Then we obtain the point spread function, a blur kernel for sparse reconstruction. We reconstruct deblurred images from the oversampled C-scan images based on l1-norm regularization, which can enhance the signal-to-noise ratio and improve the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Consequently, there is always a compromise between the resolution and the penetration depth. There is an ongoing research to combine SAM and wave propagation modelling to better understand the trade-off between the resolution and the penetration depth [ 54 , 55 ].…”
Section: Ndt Methods For Ic Packagingmentioning
confidence: 99%
“…Consequently, there is always a compromise between the resolution and the penetration depth. There is an ongoing research to combine SAM and wave propagation modelling to better understand the trade-off between the resolution and the penetration depth [ 54 , 55 ].…”
Section: Ndt Methods For Ic Packagingmentioning
confidence: 99%
“…The longitude wave velocity in water is 1480 m/s and shear wave velocity in steel is 3230 m/s. The excitation signal applied to the external circuit is a broadband modulated pulse, which can be modeled as a Gabor function [35]:…”
Section: Two-dimensional Rough Surface Model Setupmentioning
confidence: 99%
“…Acanning acoustic microscopy, as a new detection technology, can penetrate the opaque materials of certain thickness such as metal, plastic, ceramics and biological tissues. It is likely for it to reckon the size and depth of defects based on the echo energy and time difference in order to accurately locate defects and provide strong support for subsequent analysis of product defects and quality improvement [8][9][10][11][12][13]. Elena Maeva made a detection on biotissue histology of breast cancer using 200MHz ultrasonic wave and found that the lateral resolution was less than 50μm [14].…”
Section: Introductionmentioning
confidence: 99%